Institutional Economics: Rhetoric and Myths - B. A. Yerznkyan (Управление)
This article analyzes the application of rhetoric in institutional economics interpreted in various – evaluative, disciplinary, instrumental – aspects. When considering the rhetoric with the evaluative position the emphasis is done not on the positive and neutral, but on its negative – for the recipients – treatment. In terms of disciplinary or specific scientific fields, the main attention is paid to the system, as well as evolutionaryinstitutional approach. A detailed analysis of rhetorical instruments that serve as a tool for manipulating the target audience is done. On the example of the study of place and role of cultural code in economic research it is shown by which rhetorical means myths are introduced into scientific circulation.